Parallel reductions of IgE and exhaled nitric oxide after optimized anti‐inflammatory asthma treatment. Issue 2 (21st March 2016) - Syk, Jörgen; Malinovschi, Andrei; Borres, Magnus P.; Undén, Anna‐Lena; Andreasson, Anna; Lekander, Mats; Alving, Kjell
Abstract: Immunoglobulin E (IgE) is crucial for the development of airway inflammation in atopic asthma, and inhibition of IgE using monoclonal antibodies is now part of asthma therapy. However, the impact of ordinary anti‐inflammatory treatment on IgE is unclear. The aim of this study was to investigate if optimization of treatment with inhaled corticosteroid (ICS) and leukotriene‐receptor antagonist (LTRA) according to symptoms or exhaled nitric oxide (FE NO) levels over a one‐year period affects IgE concentrations. Altogether, 158 relatively well‐controlled but multi‐sensitized asthmatics (age 18–65 years), with ongoing ICS treatment at baseline, were included in this post hoc analysis of data from a randomized, controlled trial on FE NO‐guided asthma therapy. Asthma control and quality of life (Juniper ACQ and mAQLQ), FE NO, and serum IgE were measured at baseline and after one year. Concentrations of IgE antibodies to six common perennial aeroallergens were summed up (perennial IgE). We found that perennial and total IgE decreased by 10.2% and 16.0% ( P < .001 both comparisons). This was not related to allergen exposure, whereas the total use of ICS and LTRA during the year correlated with the reduction in perennial IgE ( P = .030 and P = .013). The decrease in perennial and total IgE correlated significantly with the reduction in FE NO ( P < .003 and P < .001), and with improvements in ACQ and mAQLQ scores ( P < 0.05, all comparisons). We conclude that one year of optimization of treatment with ICS and LTRA in patients with persistent atopic asthma resulted in significant decreases in total IgE and IgE antibodies; these decreases correlated with a reduction in FE NO and improvements in asthma control and quality of life. Thus, IgE is reduced by ordinary asthma controller medications and the effect on IgE seems to be clinically important. Abstract : This is the first study to show a parallel reduction in IgE concentrations and FeNO, a marker of Th2‐driven airway inflammation, by ordinary controller medication in patients with allergic asthma. The reduction in IgE was larger in patients showing a clinically important improvement of asthma control. We suggests that IgE measurement may be used in the long‐term follow up of anti‐inflammatory asthma treatment.